Growth Response of Patchouli Plant Cuttings (Pogostemon Cablin Benth.) to Eggshell Waste as Liquid Organic Fertilizer: Respons Pertumbuhan Stek Tanaman Nilam (Pogostemon Cablin Benth.) terhadap Pemberian Limbah Cangkang Telur sebagai Pupuk Organik Cair - Indriani; Najoan, Jemmy; Pakasi, Sandra (Jurnal Lentera Hijau Indonesia, 2026)
Patchouli (Pogostemon cablin Benth.) is a high-value essential oil-producing plant that is increasingly being cultivated in North Sulawesi. Expanding cultivation areas necessitates the production of seedlings via cuttings, yet low soil fertility often hinders growth. This study aimed to evaluate the growth response of patchouli cuttings to the application of liquid organic fertilizer (LOF) derived from eggshell waste and to determine the optimal concentration. A Randomized Block Design (RBD) was employed, featuring six treatments (0%, 12.5%, 25%, 37.5%, 50%, and 62.5% LOF) and four replications across 144 plants. The results indicated that the eggshell waste LOF significantly influenced root number, root length, root weight, shoot number, leaf count, and the weight of the patchouli cuttings. The calcium, nitrogen, phosphorus, and potassium content in eggshells plays a crucial role in stimulating vegetative growth and root system development, while also offering the potential to improve soil pH. The 62.5% concentration (P5) yielded the best results across all growth parameters (with the exception of the time to root emergence, which showed no statistically significant difference). Thus, eggshell waste LOF serves as an effective, eco-friendly organic fertilizer solution for patchouli seedling propagation.Keywords: egg shell, cutting, liquid organic fertilizer, patchouli